Determinants of the Limpopo Province of South Africa’s response to COVID-19 : a mixed methods protocol to analyze and share lessons learned - Matlala, Sogo F.; Tshitangano, Takalani G.; Setati, Musa E.; Ramalivhana, Naledzani J.; Mphekgwana, Peter M. (My University, 2022)
COVID-19 is a priority health research agenda item in South Africa. The World Health Organization declared the COVID-19 outbreak as a Public Health Emergency of International Concern, which requires all countries to respond and share data with others. Responses included the implementation of measures to reduce the spread of COVID-19 and protect health systems from being overwhelmed by seriously ill patients. Each country was mandated to assess its own risk and rapidly implement the necessary measures to reduce COVID-19 transmission and minimize its impact. Countries were further encouraged to share their experiences of responding to the COVID-19 pandemic. Media reports in South Africa suggest that the Limpopo Department of Health implemented a successful COVID-19 response. This study aims to analyze, document and publish those successes to make them accessible to other researchers and public health practitioners. The study will also allow for the participation of public health students to meet the requirements of their postgraduate degrees. This convergent parallel mixed method study will collect secondary data of responses to COVID-19 by the Limpopo Department of Health from the records the department keeps. Quantitative and qualitative data detailing activities and statistics describing facilitators and barriers to implementation of COVID-19 response from March 2020 will be extracted from records.
Journal article published in the Journal of Healthcare 2022, 10, 926
Keywords: Secondary data; COVID-19; Lessons learned; COVID-19 (Disease)